PEMBELAJARAN BERBASIS PRAKTIKUM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Ariyati, Eka (Universitas Tanjungpura, 2010)
The aim of this research is to know the improvement of critical thinking ability of pre-service teacher students on Ecosystem and Biodiversity concepts after applying practicum based learning. The method of this research is quasi-experiment with the one group pretest-postest design. The sample were 2nd semester pre-service teacher students at biology education department that following the Environmental Science Course at FKIP Tanjungpura University, consist of 34 students. Data were collected through multiple choice test with reasoning and essay test, and were analyzed by using mean-difference test and normalized gain score. The result of gain score show that critical thinking ability were improve (0,39) through this learning model. Conclusion of this research, practicum based learning give positive influence to critical thinking ability of pre-service teacher students.Keywords : practicum based learning, critical thinking ability